Internetordbøgers layout - Almind, Richard; Bergenholtz, Henning (Nordiske Studier i Leksikografi, 2003)
Layout in Internet Dictionaries Compared to the layout of internet dictionaries the layout in printed dictionaries is rather acceptable, although still seldom perfect. The reason for this being that the HTML-code used to present text on screen simply doesn’t provide the necessary tools for proper control of typography. The portal YourDictionary.Com informs us that it contains links to more than 230 dictionaries on the net. A swift inspection proves that most of these so-called dictionaries are mere word lists. All of them primitive lexicographically, but showing a greater disrespect to simple layout-principles even by HTML-standards. Of the remaining handful internet dictionaries that have an acceptable layout – or rather a certain minimum of aesthetic acceptability – most are converted printed dictionaries containing the ”original” typography but subjected to HTML as far as possible and thus with little success. The smallest part of that handful are new dictionaries made for the internet directly and are still not optimal in their layout but at least make the effort. It will be shown that very few rules have to be taken into consideration to create an internet dictionary in order for it to be both aesthetically pleasing and of practical use.